Genetically distinct populations of northern shrimp, Pandalus borealis, in the North Atlantic: adaptation to different temperatures as an isolation factor. Issue 8 (6th April 2015) - Jorde, Per Erik; Søvik, Guldborg; Westgaard, Jon‐Ivar; Albretsen, Jon; André, Carl; Hvingel, Carsten; Johansen, Torild; Sandvik, Anne Dagrun; Kingsley, Michael; Jørstad, Knut Eirik
Abstract The large‐scale population genetic structure of northern shrimp, Pandalus borealis, was investigated over the species' range in the North Atlantic, identifying multiple genetically distinct groups. Genetic divergence among sample localities varied among 10 microsatellite loci (range: FST = −0.0002 to 0.0475) with a highly significant average (FST = 0.0149; P < 0.0001). In contrast, little or no genetic differences were observed among temporal replicates from the same localities (FST = 0.0004; P = 0.33). Spatial genetic patterns were compared to geographic distances, patterns of larval drift obtained through oceanographic modelling, and temperature differences, within a multiple linear regression framework. The best‐fit model included all three factors and explained approximately 29% of all spatial genetic divergence. However, geographic distance and larval drift alone had only minor effects (2.5–4.7%) on large‐scale genetic differentiation patterns, whereas bottom temperature differences explained most (26%). Larval drift was found to promote genetic homogeneity in parts of the study area with strong currents, but appeared ineffective across large temperature gradients. These findings highlight the breakdown of gene flow in a species with a long pelagic larval phase (up to 3 months) and indicate a role for local adaptation to temperature conditions in promoting evolutionary diversification and speciation in the marine environment.